2002
DOI: 10.1143/jjap.41.3943
|View full text |Cite
|
Sign up to set email alerts
|

Generation Of High Energy Ion Beams from a Plasma Focus Modified for Low Pressure Operation

Abstract: This paper reports on the modification of a small plasma focus device (UNU/ICTP PFF) to operate at low pressure for enhanced ion beam generation. For the present operation, the electrode geometry of the plasma focus device is modified to redirect the plasma motion at the end of the axial rundown phase so that normal plasma focus action will not occur. The redirection of the plasma leads to a rapid increase in the plasma resistivity and hence a high localized electric field will be established and as a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 7 publications
(7 reference statements)
1
18
0
Order By: Relevance
“…The second strong spike/peak is only due to the ions of PF device. The ion beam signals with similar type of characteristics were also reported by earlier workers 18,29,30 where the small hump is identified as due to EM radiation rather than ion beam. We have carried out experiment by blocking the pinhole of FC in order to check the response of x-ray radiation onto the part of transmission line that is inside the PF chamber and the corresponding FC signal along with the dI / dt signal is illustrated in Fig.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The second strong spike/peak is only due to the ions of PF device. The ion beam signals with similar type of characteristics were also reported by earlier workers 18,29,30 where the small hump is identified as due to EM radiation rather than ion beam. We have carried out experiment by blocking the pinhole of FC in order to check the response of x-ray radiation onto the part of transmission line that is inside the PF chamber and the corresponding FC signal along with the dI / dt signal is illustrated in Fig.…”
Section: Resultssupporting
confidence: 83%
“…Sadowski et al described that the intensity of the ion beams depends on the electrode geometry, bank energy, and working gas type, as well as pressure. 17 Wong et al 18 modified their PF device to produce highenergy ion beam of nitrogen, argon, and hydrogen in a lowpressure mode and they suggested that the generation of a high local electric field due to the rapid increase in the plasma resistivity accelerates the ion beam to high energy. Zakaullah et al 19 observed a good agreement on time evolution of the x-ray, electron, ion, and voltage probe signals in an argon filled 3.6 kJ PF device.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the plasma focus is a transient plasmaproducing device that makes use of a self-generated magnetic field to pinch the plasma to a high dense and hot plasma column. During the pinching, the temperature of the plasma becomes so high that the bulk amount of the electromagnetic radiation lies in the X-ray range [3,4] and, after the disruption of pinch column, the energetic electrons and ions having broad ionization states are emitted [5,6]. The direction of the emission of electrons and ions are opposite to each other and it is towards the anode for electrons.…”
mentioning
confidence: 99%
“…Some examples of the registered traces of the collector signals are presented in Figure 3. The velocity, energy and density of helium ions are estimated using TOF technique (Gerdin et al, 1981;Wong et al, 2002). The ion velocity is estimated by taking the ratio of the distance to the flight time of ions from source to detector (Lee and Saw, 2013).…”
Section: Resultsmentioning
confidence: 99%